(untitled) (Research, Society and Development, 2021)
This research aims to identify and analyze which public educational policies guide emergency remote teaching during the Covid-19 pandemic in the city of Jaguarão/RS. Therefore, a study was carried out in official documents dealing with this theme. Methodologically, the nature is classified as qualitative and procedurally it is a documentary research, and the technical-methodological analysis is based on Content Analysis. The theoretical bases were based on Almeida (2018), Arruda (2020), Martins (2013), Saviani & Galvão (2021), and others. Conclusions show that the current strong aggravating factor in the educational field for the development of remote learning is the inequality in the conditions of access and use of resources and devices available on the internet. It also points to the urgency in the construction of public policies that bring to the studied educational scenario, greater investments in information and communication technologies in public basic education networks correlated to the creative teaching and learning processes.